Analysis of Rhetorical Moves and Linguistic Realization of Research Article Abstract in Islamic Studies - Acep Haryudin (Jurnal Perspektif, 2023)
This study investigates the rhetorical movement of research article abstracts (RAA) and analyzes the language features used to achieve rhetorical moves. Genre analysis (move analysis) and corpus linguistics approach were employed to examine the rhetorical moves in RAA and to investigate the language features used to achieve moves in Islamic studies RAA. The corpus made in the present study consisted of 20 RAA taken from 5 reputable international journals in Islamic studies indexed by Scopus. Several stages were conducted to analyze the data using Hyland's (2000) framework model. The results of the study show that Hyland’s model of rhetorical move occur in RAA in the corpus. Some RAA applied at least three moves and others used all five moves. Out of five moves, M2 and M4 are deployed in all RAA in the corpus and they can be considered obligatory moves. Regarding linguistic realization, voice and tense were used to achieve rhetorical moves of RAA in Islamic studies.  Pedagogically speaking, this research is expected to provide important information regarding rhetorical movement and language features in writing RAA in the field of Islamic studies. This scholarly information may assist early career researcher in Islamic studies to write their research article before submitting to international reputable journals.